If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -125 = 2x + -9 Reorder the terms: -125 + 6x = 2x + -9 Reorder the terms: -125 + 6x = -9 + 2x Solving -125 + 6x = -9 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -125 + 6x + -2x = -9 + 2x + -2x Combine like terms: 6x + -2x = 4x -125 + 4x = -9 + 2x + -2x Combine like terms: 2x + -2x = 0 -125 + 4x = -9 + 0 -125 + 4x = -9 Add '125' to each side of the equation. -125 + 125 + 4x = -9 + 125 Combine like terms: -125 + 125 = 0 0 + 4x = -9 + 125 4x = -9 + 125 Combine like terms: -9 + 125 = 116 4x = 116 Divide each side by '4'. x = 29 Simplifying x = 29
| 5x-17=x+17 | | b=3v-h | | 4x^3-24x^2+x=0 | | ln(x)-ln(6)=(16) | | 3(2x+4)=5(x-4) | | -4(2y+4)-1=-4(y+8)+2y | | 12a^6-8a^3= | | -3x-34(x+3)=-9(4x+2) | | 2x+1x=3 | | 4(x+3)+9=13 | | 6z+2=1 | | -2x+25=9 | | ln(2x+9)+ln(3)=2ln(x) | | -3(4-5Y)=7y+4 | | x^4-8x^2+9=0 | | -10=8-(9-A) | | 20=5-(Z+6) | | 20=5-z+6 | | -5(4+r)=25 | | -7+[(1-11)-(-1-3)]= | | 5x-9+5x=-29 | | -7[(1-11)-(-1-3)]= | | -2p+5=15 | | 30-3x[8-2x(3+1)]= | | -p+5=15 | | cosx=1-m^2 | | -17-(-8)+(-3)-18= | | y=-3(-6)+3 | | 2x+34x=123 | | 9=5y | | -8+-7= | | a+3a=372 |